2016
DOI: 10.1016/j.socscimed.2016.02.030
|View full text |Cite
|
Sign up to set email alerts
|

A question of balance: Explaining differences between parental and grandparental perspectives on preschoolers' feeding and physical activity

Abstract: Rationale Although one quarter of US and UK families rely on grandparents as the main providers of informal childcare, grandparental perspectives on the feeding and physical activity of young children remain understudied. Objective The study's aim was to elucidate parents' and grandparents' perspectives on young children's feeding and physical activity, and identify how they negotiate potential differences between these perspectives. Methods We interviewed 22 parents and 27 grandparents from 16 families of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
129
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(144 citation statements)
references
References 50 publications
(59 reference statements)
10
129
1
Order By: Relevance
“…A total of 483 studies were identified through the search strategy, with 83 full‐text articles retrieved, of which 16 studies met the inclusion criteria and were included in the review (Figure ) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 483 studies were identified through the search strategy, with 83 full‐text articles retrieved, of which 16 studies met the inclusion criteria and were included in the review (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…Studies were published between 2007 and 2016 in the USA (n = 6), China (n = 3), Greece (n = 2), Australia (n = 2), Canada (n = 2) and Japan (n = 1) . Studies included in the review included grandparents as the primary study population (n = 2), children as the primary study population (n = 5) or a combination of grandparents, parents and children (n = 9) . The studies therefore included a range of family structures, cultural groups and food availability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited literature on grandparent feeding practices suggests that grandparents engage in more maladaptive feeding practices (Eli, Howell, Fisher, & Nowicka, 2016), though there is a positive association with time spent providing care and adaptive practices (Farrow, 2014). As with much of the research in this domain, studies have tended to focus on younger children.…”
Section: Discussionmentioning
confidence: 99%
“…While grandparents in high‐income countries are generally better educated and healthier than grandparents in low‐income countries, generation gaps in child‐rearing practices still exist. Parents complain about grandparents for promoting snack consumption and being lax about screen time . Grandparent involvement in childcare during infancy is reported to increase the risk of obesity and BMI in preschool children .…”
Section: Introductionmentioning
confidence: 99%